2021
DOI: 10.1007/s11136-021-03038-2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of body mass index since childhood and health-related quality of life in young adulthood: Tehran Lipid and Glucose Study

Abstract: Purpose The association between long-term BMI changes since childhood and health-related quality of life (HRQoL) in adulthood is still unclear. This study aimed to examine the association between identified BMI trajectories and HRQoL. Methods A population-based cohort of 1938 eligible children (3-18 years) and their parents have been repeatedly followed up for 18 years. Offspring BMI trajectories were identified using group-based trajectory models. HRQoL was evaluated in offspring aged 21-36 years using SF-12V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 100 publications
3
13
0
Order By: Relevance
“…Although the second large subpopulation identified in our analysis was normal weight in childhood, it transitioned to overweight in young adulthood. In the previous study on the TLGS population, three BMI trajectories were identified as normal, overweight, and increasing overweight/obese [30]. However, the current study allowed us to differentiate two subgroups (ECOAO and ECO) from the previous increasing overweight/obese group with a larger sample size.…”
Section: Discussionmentioning
confidence: 78%
“…Although the second large subpopulation identified in our analysis was normal weight in childhood, it transitioned to overweight in young adulthood. In the previous study on the TLGS population, three BMI trajectories were identified as normal, overweight, and increasing overweight/obese [30]. However, the current study allowed us to differentiate two subgroups (ECOAO and ECO) from the previous increasing overweight/obese group with a larger sample size.…”
Section: Discussionmentioning
confidence: 78%
“…Participants were sampled from 14 different cohorts, with the Northern Finland 1966 Birth Cohort, 21,48 the National Longitudinal Study of Adolescent Health cohort 41,45 and the Cardiovascular Risk in Young Finns cohort, 16,29 generating two publications each. Cohorts were from the United States ( n = 3), 35,41,45 the United Kingdom ( n = 3), 25,31,50 Finland ( n = 4), 16,21,29,48 Spain ( n = 1), 27 Canada ( n = 1), 44 Australia ( n = 2), 13,46 France ( n = 1), 39 and Iran ( n = 1) 23 . Most articles studied both men and women, except for three which exclusively sampled females 13,39,41 .…”
Section: Resultsmentioning
confidence: 99%
“…Eleven 13,16,21,31,35,41,44–46,48,50,53 defined weight change between two time points, and the remaining six 23,25,27,29,37,39 defined trajectories of weight change based on three or more repeated measures of weight. Two 29,37 of these articles modelled population‐average trajectories using generalized estimating equations, and four 23,25,27,39 articles modelled heterogenous person‐centered trajectories using growth mixture modelling 25 or group‐based trajectory modelling 23,27,39 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations